Isolation and Characterization of Metal Resistance Genes by using Metatranscriptomic Approach - Manpreet, Kour (My University, 2014)
Metatranscriptomics is a recent culture-independent approach in microbial ecology which gives a direct and simultaneous access to the genes expressed by all the microbial species, cultivable or not, living in a common environment. This approach has a strong potential in biotechnology to discover novel genes of interest for the bio-industry, in bioremediation and as biomarkers. In the present study, Functional metatranscriptomics approach was adopted to isolate and characterize metal resistance genes expressed by eukaryotic species in the heavy metal polluted environment. The total RNA was isolated from heavy metal polluted soil. The eukaryotic mRNAs, owing to their 3ʹ poly-A tails were specifically converted into intron-less cDNAs. These cDNAs were size fractionated, cloned to generate environmental metatranscriptomic cDNA libraries, which are representative of the fraction of protein-coding genes expressed at the time of sampling. These cDNA libraries were constructed in the modified pFL61 yeast-E. coli shuttle vector. The metatranscriptomic libraries were screened for the presence of metal resistance genes by functional complementation of Saccharomyces cerevisae mutants. The mutant strains, copper sensitive cup1∆ and cadmium sensitive ycf1 were used in this study. Yeast transformants exhibiting metal resistance were identified by plating on medium supplemented with either copper or cadmium and further characterized by studying their growth curve in the presence of metal.
MT, DBTS
Keywords: metatranscriptomics, cadmium, copper, Zinc, yeast complemnetation, metal tolerance